2021
DOI: 10.3389/fcvm.2021.765749
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in High-Density Lipoprotein Quantity and Quality Contribute to the Cardiovascular Benefits by Anti-tumor Necrosis Factor Therapies in Rheumatoid Arthritis: A Systemic Review and Meta-Analysis

Abstract: Objective: Inflammation plays important role in atherosclerotic cardiovascular diseases (CVDs), but the interaction between the inflammation and lipid profile is largely unrevealed in humans. Patients with rheumatoid arthritis (RA) suffer from a higher risk of CVDs. Decreased total cholesterol (TC) and high-density lipoprotein (HDL) were prevalent in patients with RA. Anti-tumor necrosis factor (TNF) therapies relieve disease activity and decrease CVDs risk in RA, but their comprehensive effects on the lipid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…On the contrary, DMARDs or biological therapies can also influence the functionality of lipoproteins, although there are few studies on this topic and with contradictory results. 52,53 Regarding biological therapies, Popa et al described a beneficial effect on HDL antioxidative capacity that significantly improved after anti-tumour necrosis factor therapy with infliximab. 54 Differing from these previous findings, the present study found no differences in relation to biological therapies and functional lipid metabolism in RA patients, or with the presence or not of plaque or with the cIMT value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, DMARDs or biological therapies can also influence the functionality of lipoproteins, although there are few studies on this topic and with contradictory results. 52,53 Regarding biological therapies, Popa et al described a beneficial effect on HDL antioxidative capacity that significantly improved after anti-tumour necrosis factor therapy with infliximab. 54 Differing from these previous findings, the present study found no differences in relation to biological therapies and functional lipid metabolism in RA patients, or with the presence or not of plaque or with the cIMT value.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we observed in the current study that patients with plaque were taking a significantly lower equivalent dose of prednisone than those without plaque. On the contrary, DMARDs or biological therapies can also influence the functionality of lipoproteins, although there are few studies on this topic and with contradictory results 52,53 . Regarding biological therapies, Popa et al described a beneficial effect on HDL antioxidative capacity that significantly improved after anti‐tumour necrosis factor therapy with infliximab 54 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a direct correlation between serum TNF‐α and plasma triglyceride levels in adolescents with CF has been described by Levy et al, 139 although the finding was not confirmed in another study 145 . In patients with Crohn's disease and rheumatoid arthritis, anti‐TNF therapies can be associated with increased total and HDL cholesterol 170,171 . A retinoic acid analog (fenretinide) and antioxidants (glutathione and deferoxamine) with anti‐inflammatory activities also have been shown to partially correct oxidative stress and lipid imbalance in CFTR‐deficient epithelial cells 172 …”
Section: Pathophysiology Of the Cf Gi Tractmentioning
confidence: 97%
“…145 In patients with Crohn's disease and rheumatoid arthritis, anti-TNF therapies can be associated with increased total and HDL cholesterol. 170,171 A retinoic acid analog (fenretinide) and antioxidants (glutathione and deferoxamine) with anti-inflammatory activities also have been shown to partially correct oxidative stress and lipid imbalance in CFTR-deficient epithelial cells. 172 The prevalence of dyslipidemias is likely to increase in the era of highly effective CFTR modulators because life expectancy of pwCF is steadily increasing.…”
Section: Effect Of Cftr Modulators On Dyslipidemiamentioning
confidence: 99%